2003
DOI: 10.1289/ehp.5866
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal examination of factors related to changes in serum polychlorinated biphenyl levels.

Abstract: Consumption of sport-caught fish from the Great Lakes is a recognized source of human exposure to polychlorinated biphenyls (PCBs). Understanding temporal changes in PCB body burden is crucial for evaluating exposure levels and augmenting validity of studies investigating their relationship to adverse health effects. Using data collected from 1980 to 1995, we evaluated longitudinal changes in serum PCB levels among 179 fisheaters and non-fisheaters of the Michigan Fisheater Cohort. Participants identified as f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 47 publications
3
30
0
Order By: Relevance
“…Human activities not only affect these mechanisms but also determine contact with the resulting concentrations. Longitudinal investigations of the activities that influence changes in contaminant levels over time are scarce but are necessary to increase our understanding of the role they might play in the risk of adverse health outcomes (Tee et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Human activities not only affect these mechanisms but also determine contact with the resulting concentrations. Longitudinal investigations of the activities that influence changes in contaminant levels over time are scarce but are necessary to increase our understanding of the role they might play in the risk of adverse health outcomes (Tee et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, findings from a cohort of older participants (≥ 50 years of age in 1992) recently demonstrated that a reduction in current fish consumption was associated with a monotonic decline in PCB levels in blood serum (Tee 2003). Although self-reported fish consumption has substantially declined over time, sport-caught fish intake continues to be one of the key predictors of serum PCB levels Humphrey et al 2000;Tee 2003 breast milk, or adipose tissue in various populations (Dallaire et al 2002;Fitzgerald et al 1999;Hovinga et al 1992;Konishi et al 2001;Noren and Meironyte 2000;Robinson et al 1990;Smith 1999). According to Noren and Meironyte (2000), the level of organochlorine compounds in 1997 was approximately one-tenth of the 1972 level in breast milk from Swedish mothers living in the Stockholm region.…”
Section: Discussionmentioning
confidence: 91%
“…The level of PCBs in serum sampled from a general population of men and women in Michigan significantly declined from 1979 to 1989 (Humphrey et al 2000); however, levels remained virtually unchanged in sport-caught fish consumers. In contrast, findings from a cohort of older participants (≥ 50 years of age in 1992) recently demonstrated that a reduction in current fish consumption was associated with a monotonic decline in PCB levels in blood serum (Tee 2003). Although self-reported fish consumption has substantially declined over time, sport-caught fish intake continues to be one of the key predictors of serum PCB levels Humphrey et al 2000;Tee 2003 breast milk, or adipose tissue in various populations (Dallaire et al 2002;Fitzgerald et al 1999;Hovinga et al 1992;Konishi et al 2001;Noren and Meironyte 2000;Robinson et al 1990;Smith 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Hanrahan study conducted in 1993-1994, male fish-eaters had a mean serum PCB level of 4.8 ppb compared with 1.5 ppb among their nonconsuming counterparts (Hanrahan et al 1999), whereas female fish-eaters had levels of 2.1 ppb versus 0.9 ppb among female non-fish-eaters. Participants in the Michigan fish-eaters cohort, which consists of individuals who were consuming ≥ 26 pounds of sport-caught fish per year (fish-eaters) and those eating < 6 pounds per year (non-fish-eaters), when enrolled in 1980, had considerably higher serum PCB levels (Tee et al 2003).…”
Section: Compounds In the Femalementioning
confidence: 99%